PENGEMBANGAN ALAT UKUR KUALITAS HIDUP INDONESIA - Resmiya, Latifa; Misbach, Ifa Hanifah (Program Studi Psikologi Universitas Pendidikan Indonesia, 2019)
This research aimed to develop a Kualitas hidup measurement tool in Indonesia. The research method used in this study is a combined method of qualitative and quantitative research (mixed method). The qualitative stage aimed at exploring the theme of kualitas hidup totaling 250 people. Meanwhile, participants in the quantitative stage aimed at identifying psychometric properties (validity and reliability) numbered 759 people. The data analysis technique used for qualitative data is open coding. Quantitative data consists of construct validity test using factorial validity with exploratory factor analysis (EFA), convergent validity, and known-group validity, and estimation of internal consistency reliability using Cronbach's Alpha. The EFA results show that the Kualitas hidup Indonesia measuring instrument consists of 9 factors and 30 items with a very high reliability coefficient (.88). Convergent validity in this study was carried out by correlating the Kualitas hidup Indonesia measuring tool with the WHOQOL-BREF measurement tool. Validity by known-group is done by comparing demographic data of age, sex, marital status, education level, employment status, and health conditions using One Way ANOVA.